Adult and embryonic blood and endothelium derive from distinct precursor populations which are differentially programmed by BMP in Xenopus. - Walmsley, M; Ciau-Uitz, A; Patient, R (2002)
Blood and blood vessels develop in close association in vertebrate embryos and loss-of-function mutations suggest common genetic regulation. By the criteria of co-expression of blood and endothelial genes, and lineage tracing of progeny, we locate two distinct populations of progenitors for blood and endothelial cells in developing Xenopus embryos. The first population is located immediately posterior to the cement gland during neurula stages and gives rise to embryonic blood and vitelline veins in the anterior ventral blood island (aVBI), and to the endocardium of the heart. The second population resides in the dorsal lateral plate mesoderm, and contains precursors of adult blood stem cells and the major vessels. Both populations differentiate into endothelial cells in situ but migrate to new locations to differentiate into blood, suggesting that their micro-environments are unsuitable for haematopoietic differentiation. Both require BMP for their formation, even the Spemann organiser-derived aVBI, but individual genes are affected differentially. Thus, in the embryonic population, expression of the blood genes, SCL and GATA2, depend on BMP signalling while expression of the endothelial gene, Xfli1, does not. By contrast, Xfli1 expression in the adult, DLP population does require BMP. These results indicate that both adult and the anterior component of embryonic blood in Xenopus embryos derive from populations of progenitors that also give rise to endothelial cells. However, the two populations give rise to distinct regions of the vasculature and are programmed differentially by BMP.